The National Budget Circular 461: Emerging trends in Philippines higher education promotion system - Francisco D. Esponilla II; Lean Karlo S. Tolentino; Cherrypyn B. Barbacena; Apollo P. Portez (International Journal of Evaluation and Research in Education (IJERE), 2020)
This research aimed to identify trends on promotion challenges and concerns (CaCs) encountered by the faculty members in selected State universities and colleges (SUCs) in the Philippines. To specifically identify significant CaCs, the study employed the mixed-method research design utilizing the delphi model technique for data collection. Thematic data coding was thoroughly conducted to come up with a consensus from the experts in the field of promotion in higher education. There were 10 focal persons from the SUCs in the national capital region (NCR) purposively chosen as the study participants. The identified challenges and concerns as the trend indicators were categorized into themes such as appreciation of documents, faculty engagement for promotion, information dissemination, schedule of implementation, responsiveness of the national budget circular No. 461 (NBC 461) focal persons to promotion-related concerns, faculty engagement to promotion, and stakeholder’s engagement to promotion. These indicators would be a relevant implication to the holistic and a uniform faculty promotion scheme in higher education institutions of the country. Hence, the result of the study shall be utilized by the SUCs policymakers in crafting the standardized NBC 461 policy guideline that is inclusive for implementing equal promotion opportunity as well as job security.